Transfer of Training in Malaysian TVET Institutions: The Role of Attitude, Organisational Commitment, Perceived Importance and Gender Differences (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Technical and Vocational Education and Training (TVET) is a central pillar of Malaysia’s human capital development strategy, particularly in producing industry-ready graduates aligned with Industry 4.0 requirements. The effectiveness of this system is highly dependent on TVET lecturers’ ability to transfer training outcomes into actual teaching practice. However, despite substantial investment in professional development, training transfer among lecturers remains inconsistent and insufficiently examined. This conceptual paper proposes a study involving TVET lecturers in Malaysian higher learning institutions as respondents to investigate transfer of training. The study is guided by three objectives: (i) to assess the level of training transfer, (ii) to examine gender differences, and (iii) to determine the influence of attitude, organisational commitment, and perceived importance on training transfer. The study is underpinned by the Theory of Planned Behaviour (TPB), which explains how attitude, organisational commitment, and perceived importance shape behavioural intention and subsequently influence training transfer. Gender Role Theory is integrated to account for possible gender-based differences, particularly in male-dominated technical fields such as automotive and mechanical engineering. A quantitative cross-sectional survey design is proposed, with data analysed using descriptive statistics, independent sample t-tests, and multiple regression analysis via SPSS. This study is expected to extend the literature by integrating TPB and Gender Role Theory in explaining training transfer among TVET lecturers in Malaysia, while providing practical implications for enhancing the effectiveness of professional development programmes.